“Examining the Incorporation of Islamic Values in Concept Mapping and Curriculum Design for Medical Education: A Holistic Perspective” (Bangladesh Journal of Medical Science, 2024)
Medical education is an ever-evolving realm, continuously striving for innovative methods to improve learning outcomes and nurture competent healthcare practitioners. Concept mapping has emerged as a valuable tool in this drive, aiding in the organization and synthesis of intricate information. This review delves into the infusion of Islamic teachings into concept map teaching and curriculum development within medical education. By drawing on Islamic principles related to knowledge acquisition, ethics, and comprehensive healthcare, this examination offers strategies for integrating Islamic perspectives into concept mapbased teaching approaches. Through harmonizing educational practices with Islamic ethos, medical educators can cultivate an environment that is culturally attuned and ethically rooted, fostering the development of healthcare professionals who embody compassion and integrity in serving their communities.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 984-992